Evidence that a working memory cognitive phenotype within schizophrenia has a unique underlying biology. (November 2022) - Dean, Brian; Thomas, Elizabeth H.X.; Bozaoglu, Kiymet; Tan, Eric J.; Van Rheenen, Tamsyn E.; Neill, Erica; Sumner, Philip J.; Carruthers, Sean P.; Scarr, Elizabeth; Rossell, Susan L; Gurvich, Caroline
Highlights: A sub-group within schizophrenia has been identified defined because they have with impaired working memory (IWM). Using Affymetrix™ Human Exon 1.0 ST Arrays, levels of 72 RNAs were higher in blood from patients with IWM compared to a group with schizophrenia without impaired working memory. In the IWN, there were higher levels of RNA from 11 genes with a proven link to the maintenance of different aspects of working memory (cognition). Differentially expressed genes in IWN included RAS-like, estrogen-regulated, growth inhibitor ( RERG ) which is associated with cognitive ability as well as genes involved in glutamatergic activity, olfaction, immunity, inflammation as well as energy and metabolism. Abstract: It is suggested studying phenotypes within the syndrome of schizophrenia will accelerate understanding the complex molecular pathology of the disorder. Supporting this hypothesis, we have identified a sub-group within schizophrenia with impaired working memory (WM) and have used Affymetrix™ Human Exon 1.0 ST Arrays to compare their blood RNA levels (n=16) to a group of with intact WM (n=18). Levels of 72 RNAs were higher in blood from patients with impaired WM, 11 of which have proven links to the maintenance of different aspects of working memory (cognition). Overall, changed gene expression in those with impaired WM could be linked to cognition through glutamatergic activity, olfaction, immunity, inflammation as well as energy and metabolism. Our data gives preliminary support to the hypotheses that there is a working memory deficit phenotype within the syndrome of schizophrenia with has a biological underpinning. In addition, our data raises the possibility that a larger study could show that the specific changes in gene expression we have identified could prove to be the biomarkers needed to develop a blood test to identify those with impaired WM; a significant step toward allowing the use of personalised medicine directed toward improving their impaired working memory.